2015
DOI: 10.3791/53541
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Early Steps of Ovarian Cancer Dissemination in an Organotypic Culture of the Human Peritoneal Cavity

Abstract: The pattern of ovarian cancer metastasis is markedly different from that of most other epithelial tumors, because it rarely spreads hematogenously. Instead, ovarian cancer cells exfoliated from the primary tumor are carried by peritoneal fluid to metastatic sites within the peritoneal cavity. These sites, most notably the abdominal peritoneum and omentum, are organs covered by a mesothelium-lined surface. To investigate the processes of ovarian cancer dissemination, we assembled a complex three-dimensional cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Moreover, the HIF-1 and HIF-2 targets including PGK1 and VEGFA were induced upon hypoxia treatment (Fig. 2B, (33)). In addition to mesothelial cells, HGSOC cells express HIF-1 and HIF-2 upon hypoxic treatment in vitro and in HGSCO metastases (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, the HIF-1 and HIF-2 targets including PGK1 and VEGFA were induced upon hypoxia treatment (Fig. 2B, (33)). In addition to mesothelial cells, HGSOC cells express HIF-1 and HIF-2 upon hypoxic treatment in vitro and in HGSCO metastases (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Processing of healthy omentum samples is summarised in Supplementary Figure 1 and is based on previously described methods [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…The organotypic culture was assembled as previously described [ 38 ]. NOFs (2-4×10 3 /100μl) were mixed with collagen (rat tail collagen type I, Gibco, Carlsbad, CA, USA) at a concentration of 0.5μg/100μl and plated onto a black, clear bottomed 96 well plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Customization of the model with different ECM proteins revealed that ovarian cancer cell adhesion and invasion is greatest in the presence of collagen, compared with vitronectin, fibronectin, or laminin. This tool was also shared as a JoVE video article to improve dissemination of the protocol and as a resource for other scientists in the ovarian cancer field [ 17 ].…”
Section: Three-dimensional Organotypic Model Of Human Mesotheliummentioning
confidence: 99%